Advancements of the UltraScan scientific gateway for open standards‐based cyberinfrastructures. (13th March 2014) - Memon, Shahbaz; Riedel, Morris; Janetzko, Florian; Demeler, Borries; Gorbet, Gary; Marru, Suresh; Grimshaw, Andrew; Gunathilake, Lahiru; Singh, Raminder; Attig, Norbert; Lippert, Thomas; Wilkins‐Diehr, Nancy; et al.
SUMMARY The UltraScan data analysis application is a software package that is able to take advantage of computational resources in order to support the interpretation of analytical ultracentrifugation experiments. Since 2006, the UltraScan scientific gateway has been used with Web browsers in TeraGrid by scientists studying the solution properties of biological and synthetic molecules. UltraScan supports its users with a scientific gateway in order to leverage the power of supercomputing. In this contribution, we will focus on several advancements of the UltraScan scientific gateway architecture with a standardized job management while retaining its lightweight design and end user interaction experience. This paper also presents insights into a production deployment of UltraScan in Europe. The approach is based on open standards with respect to job management and submissions to the Extreme Science and Engineering Discovery Environment in the USA and to similar infrastructures in Europe such as the European Grid Infrastructure or the Partnership for Advanced Computing in Europe (PRACE). Our implementation takes advantage of the Apache Airavata framework for scientific gateways that lays the foundation for easy integration into several other scientific gateways. Copyright © 2014 John Wiley & Sons, Ltd.